A "Not able to live anymore": Reaction of the grieving process of the elderly dealing with chronic disease - Bahtiar Bahtiar; Sahar Sahar; Junaiti Junaiti; Wiarsih Wiarsih; Wiwin Wiwin (International Journal of Nursing and Health Services (IJNHS), 2018)
Background: Psychological problems have an impact on the elderly with chronic diseases thus affecting health status. Objective: The purpose of this study was to identify the response of the elderly in dealing with chronic diseases. Methods: This study uses a descriptive phenomenology method. The population in this study were elderly who lived in Makassar City and had a chronic disease. This study illustrates the experience of 13 older adults aged 60-78 years who experience chronic disease. Results: A response felt by the elderly with chronic diseases for years, a series of grieving processes. The grieving process felt by the elderly is a psychological reaction from the suffering experienced due to symptoms and complaints of chronic illness. The series of grieving process reactions that are displayed are denial, anger, bargaining, despair, and resignation. Conclusion: The old experience with denial, anger, bargaining during chronic illness is normal. Also, the elderly could experience a desperate reaction during chronic illness due to the prolonged treatment process, and resignation reaction was a sign that the elderly were aware of the disease condition which they experienced. Recommendation: nursing intervention is needed related to grieving issues that include aspects of self, physical, social and spiritual for elderly with chronic illness. Keyword: grieving, chronic illness, elderly, family